Phthalo cyanine nanocluster photocatalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202610915681.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明主要针对酞荭类有机分子在均相光催化体系中光稳定性不足、催化剂难以从反应体系中分离,以及常规沉淀法难以控制聚集态形貌和粒径分布的技术问题,提出一种酞荭类纳米聚集体光催化剂及其制备方法和应用
(1)本发明以酞荭类化合物(如Pr-2CN)为活性组分,将其由均相分子分散态转化为水相纳米颗粒聚集态,使吸收峰红移并展宽至250-700 nm,提高了对可见光的利用。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalyst technology, specifically relating to a phthalocyanine-based nano-aggregate photocatalyst, its preparation method, and its application. Background Technology
[0002] Photocatalysis technology can drive the degradation of organic pollutants using light energy under mild conditions, and has application value in water pollution control and environmental remediation. As the core of photocatalytic degradation of organic pollutants, the photocatalyst's light absorption range, excited-state lifetime, reactive oxygen species generation capacity, and photostability directly affect the pollutant degradation efficiency. J. Water Process Eng. 2023, 54 , 104069.).
[0003] Phthalocyanines, porphyrins, and related large conjugated molecules are often used as photocatalysts due to their strong visible light absorption and tunable excited-state properties. Chem. Soc. Rev. 2022, 51 (16), 6965-7045.). Phthalocyanines are a class of nitrogen-containing planar fused-ring organic compounds, which have different core structures from phthalocyanines, but also exhibit absorption characteristics in the visible light region. However, this type of photocatalyst often faces problems such as difficulty in separation and recovery and insufficient photostability in homogeneous photocatalytic reactions. Adv. Synth. Catal. 2016, 358 , 3-25.). In homogeneous photocatalytic reactions, phthalocyanine catalysts, reactants, and products are in the same phase, resulting in high costs for catalyst separation and recovery, and easy loss and waste. Furthermore, phthalocyanine molecules undergo photolysis under continuous illumination, leading to absorption peak decay and decreased catalytic activity. To facilitate catalyst separation and recovery, researchers have developed methods to convert homogeneous organic molecules into nano-aggregates to achieve heterogeneity. However, aggregation may simultaneously alter light absorption, fluorescence emission, intersystem crossing, energy transfer, and charge transfer processes; therefore, the impact on the stability and photocatalytic activity of organic molecular photocatalysts remains difficult to predict. Existing technologies only disclose phthalocyanine molecules and their applications as p-type semiconductor materials in molecular conductors, molecular electronic devices, electrochromism, photoelectric conversion, or OLED materials. Angew. Chem. Int. Ed. 2018, 57 (47), 15384-15389.), there are no reports on the nano-aggregation state of phthalocyanine molecules, their ability to generate reactive oxygen species under visible light, and their photocatalytic degradation behavior of organic pollutants in water phase.
[0004] Currently, the preparation route of phthalocyanine iron organic photocatalysts typically involves dissolving commercial phthalocyanine iron in concentrated sulfuric acid, ultrasonicating it, and then adding it dropwise to water. The resulting phthalocyanine iron supramolecular aggregates are then obtained through centrifugation, washing, and vacuum drying. Activity evaluation of this route mainly focuses on the removal of photo-Fenton contaminants under ultraviolet light and hydrogen peroxide systems. Its raw materials, reaction media, processing steps, and catalytic mechanism differ from those of phthalocyanine-based non-metallic organic nanoparticle systems. Furthermore, traditional antisolvent precipitation methods often rely on slow diffusion or conventional stirring and mixing between solutions, making it difficult to achieve uniform local concentration gradients and supersaturation distributions. This can easily lead to asynchronous nucleation and growth, resulting in a wider particle size distribution, uncontrollable morphology, and secondary agglomeration of the obtained organic nanoparticles.
[0005] Therefore, there is an urgent need to develop a new method for preparing phthalocyanine molecules that can form nanoparticles with relatively uniform particle size, high photostability, and the ability to generate reactive oxygen species under visible light, thereby enabling their application in photocatalysis. Summary of the Invention
[0006] This invention addresses the technical problems of insufficient photostability of phthalocyanine organic molecules in homogeneous photocatalytic systems, difficulty in separating the catalyst from the reaction system, and the difficulty in controlling the morphology and particle size distribution of aggregates using conventional precipitation methods. It proposes a phthalocyanine-based nanoaggregate photocatalyst, its preparation method, and its applications. This photocatalyst uses phthalocyanine compounds (such as dicyano-substituted phthalocyanine) as the active component, directly forming an aqueous nanoparticle suspension (i.e., nanoaggregates) through continuous flow antisolvent precipitation and ultrasound-assisted self-assembly. Under visible light irradiation, it can generate reactive oxygen species and degrade organic pollutants.
[0007] To address the aforementioned technical problems, a first aspect of the present invention provides a method for preparing a photocatalyst, comprising the following steps: (1) Dissolve phthaloyl compounds in an organic solvent to obtain an organic phase solution of phthaloyl; (2) The phthalocyanine organic phase solution and the aqueous phase are respectively fed into the ultrasonic microreactor, so that the phthalocyanine compounds are precipitated in the aqueous phase by continuous flow antisolvent under ultrasonic assistance, and self-assembled to form a nanoparticle suspension, thus obtaining the photocatalyst.
[0008] This invention first dissolves phthalocyanine compounds in an organic solvent to form a phthalocyanine organic phase solution. Then, the phthalocyanine organic phase solution and the aqueous phase are separately introduced into an ultrasonic microreactor through a dual-channel injection pump. Under the combined action of the microchannel and ultrasonic cavitation, they are rapidly mixed. Through antisolvent precipitation and ultrasonic-assisted self-assembly, a nanoparticle suspension is formed. This nanoparticle suspension can generate reactive oxygen species under light conditions and be used for the degradation of organic pollutants.
[0009] The preparation method of this invention differs from the traditional strong acid treatment route of concentrated sulfuric acid stripping, drip precipitation, centrifugal washing and vacuum drying; it also differs from the slow diffusion or conventional stirring and mixing in conventional antisolvent precipitation; instead, it uses microscale confined flow field coupled with ultrasonic cavitation to enable the organic phase and aqueous phase to form a uniform supersaturated state in a short time, achieving synchronous nucleation and suppressing disordered aggregation, and directly obtaining an aqueous nanoparticle suspension.
[0010] In some embodiments of the present invention, the phthaloyl compounds include dicyano-substituted phthaloyl Pr-2CN.
[0011] In some embodiments of the present invention, the organic solvent is selected from at least one of tetrahydrofuran, acetonitrile, and N,N-dimethylformamide.
[0012] In some embodiments of the present invention, the aqueous phase is selected from deionized water or an aqueous solution containing surfactants; preferably, it is deionized water.
[0013] In some embodiments of the present invention, the surfactant is selected from hexadecyltrimethylammonium bromide, and the surfactant content in the aqueous phase is 5 × 10⁻⁶. -4 mol / L.
[0014] In some embodiments of the present invention, the concentration of the phthalocyanine organic phase solution is 1 × 10⁻⁶. -4 -1×10 -3 mol / L.
[0015] In some embodiments of the present invention, the volume ratio of the phthalocyanine organic phase solution to the aqueous phase is 1:(9-20); preferably, the volume ratio of the phthalocyanine organic phase solution to the aqueous phase is 1:(15-20).
[0016] In some embodiments of the present invention, the total flow rate of the phthalocyanine organic phase solution and the aqueous phase is 10-21 mL / min; preferably, the total flow rate of the phthalocyanine organic phase solution and the aqueous phase is 16-21 mL / min.
[0017] In some embodiments of the present invention, the power of the ultrasound is 20-30 W; preferably, the power of the ultrasound is 20-25 W.
[0018] A second aspect of the present invention provides a photocatalyst, characterized in that it is prepared by the method described in the first aspect of the present invention, wherein the photocatalyst is a nanoparticle suspension of phthalocyanine compounds in an aqueous phase. This nanoparticle suspension exhibits UV-Vis absorption in the 250-700 nm range; and displays a red-shifted and broadened absorption spectrum compared to the molecularly dispersed state in the phthalocyanine organic phase solution.
[0019] In some embodiments of the present invention, the average particle size of the nanoparticles in the nanoparticle suspension is 300-500 nm.
[0020] In some embodiments of the present invention, the nanoparticles have a rhomboid or near-rhomboid morphology. These nanoparticles are dispersed in an aqueous phase to form a suspension in which no obvious sediment is visible to the naked eye.
[0021] The third aspect of this invention provides the application of the photocatalyst described in the second aspect of this invention in the photocatalytic degradation of organic pollutants.
[0022] The photocatalyst of the present invention has good photocatalytic performance. The phthalocyanine nanoparticles in its nanoparticle suspension can generate active oxygen species under light irradiation. The active species include one or more of singlet oxygen, superoxide anion radical and hydroxyl radical.
[0023] In some embodiments of the present invention, the organic pollutant is selected from one of crystal violet, rhodamine B, and tetracycline.
[0024] In some embodiments of the present invention, the photocatalytic degradation is carried out in an air atmosphere or an oxygen-rich atmosphere without the need for additional hydrogen peroxide.
[0025] Compared with the prior art, the above-described technical solution of the present invention has at least the following technical effects or advantages: (1) The present invention uses phthalocyanine compounds (such as Pr-2CN) as active components to transform them from a homogeneous molecular dispersion state to an aqueous nanoparticle aggregate state, thereby red-shifting and broadening the absorption peak to 250-700 nm, thus improving the utilization of visible light.
[0026] (2) The present invention uses an ultrasonic microreactor and an antisolvent method to directly prepare phthalocyanine nanoparticle suspension, which is different from the traditional strong acid treatment route of concentrated sulfuric acid stripping, water precipitation, centrifugal washing and vacuum drying; it is also different from the slow diffusion or conventional stirring and mixing in conventional antisolvent precipitation. The process is mild and more suitable for the aqueous nano-preparation of organic molecular photocatalysts.
[0027] (3) The Pr-2CN nanoparticles prepared in this invention have visible light photocatalytic degradation ability for crystal violet. Under 410nm light irradiation for 1 hour, the characteristic absorption of crystal violet at 582nm decreases significantly, and the degradation rate can reach 54.6%, which is higher than the degradation rate of tetrahydroxyphenylporphyrin (THPP) nanoparticles.
[0028] (4) The photostability of the Pr-2CN nanoparticles prepared by the present invention is better than that of the tetrahydrofuran homogeneous solution. Under the same light conditions, the Soret band absorption of the Pr-2CN nanoparticles does not decrease significantly within 1 hour, while the Soret band absorption peak of the homogeneous solution decreases significantly with light exposure time.
[0029] (5) This invention demonstrates, through active oxygen detection, quenching experiments and photocatalytic degradation experiments under different atmospheres, that Pr-2CN nanoparticles can generate singlet oxygen, superoxide anion radicals and hydroxyl radicals under visible light irradiation; among which singlet oxygen and superoxide anion radicals are the main active species for the degradation of crystal violet.
[0030] (6) This invention, combined with femtosecond transient absorption spectroscopy, shows that after Pr-2CN changes from solution state to nano-aggregate state, its excited state relaxation and intersystem crossing process undergo significant changes, providing excited state kinetics basis for its improved photostability and reactive oxygen generation. Attached Figure Description
[0031] Figure 1 The UV-Vis absorption spectrum, dynamic light scattering spectrum, and photoluminescence spectrum of the Pr-2CN and THPP organic phase solutions and nanoparticle suspensions prepared in Example 1 and Comparative Example 1 are shown. Figure 2 Field emission scanning electron microscope (FESEM) images of Pr-2CN and THPP nanoparticles prepared in Example 1 and Comparative Example 1; Figure 3 The images show the physical images of the Pr-2CN nanoparticle suspensions prepared in Example 1 and Comparative Example 2. Figure 4 Schematic diagram of the photocatalytic degradation experiment of crystal violet by Pr-2CN and THPP nanoparticle suspensions prepared in Example 1 and Comparative Example 1, showing the structural formula of crystal violet; Figure 5 The graph shows the photocatalytic degradation results of crystal violet by the Pr-2CN and THPP nanoparticle suspensions prepared in Example 1 and Comparative Example 1. Figure 6 Figures showing the results of the self-photolysis experiment of crystal violet and the dark adsorption experiment of crystal violet by the Pr-2CN nanoparticle suspension prepared in Example 1; Figure 7 The results of photocatalytic degradation of crystal violet by the Pr-2CN nanoparticle suspension prepared in Example 1 under different atmospheres are shown in the figure. Figure 8 The image shows the photocatalytic degradation results of crystal violet by Pr-2CN and THPP organic phase solutions prepared in Example 1 and Comparative Example 1. Figure 9 The results of detecting singlet oxygen, hydroxyl radicals and superoxide anion radicals in the Pr-2CN nanoparticle suspension prepared in Example 1 using a fluorescent probe are shown in the figure. Figure 10 Electron paramagnetic resonance spectrum, active species quenching experiment results, and photocatalytic degradation curves of Rhodamine B and tetracycline for the Pr-2CN nanoparticle suspension prepared in Example 1; Figure 11 The diagram shows the frontier molecular orbital calculation results of the Pr-2CN nanoparticle suspension prepared in Example 1. Figure 12 The femtosecond transient absorption spectra of the Pr-2CN organic phase solution and nanoparticle suspension prepared in Example 1 are shown. Detailed Implementation
[0032] The present invention will now be described in detail with reference to embodiments to facilitate understanding of the invention by those skilled in the art. It is particularly important to note that the embodiments are merely illustrative of the invention and should not be construed as limiting the scope of protection of the invention. Non-essential improvements and adjustments made to the invention by those skilled in the art based on the above description should still fall within the scope of protection of the invention. Furthermore, all raw materials mentioned below, unless otherwise specified, are commercially available products; all process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.
[0033] The Pr-2CN used in the following examples and comparative examples was prepared according to existing disclosed methods. Angew. Chem. Int. Ed. 2018, 57 (47), 15384-15389.); The improvement of this invention is not in the synthesis of Pr-2CN molecules themselves, but in the preparation of Pr-2CN into an aqueous nanoparticle suspension by an ultrasonic microreactor and an antisolvent method, and its use in visible light-driven degradation of organic pollutants.
[0034] Example 1 A method for preparing a Pr-2CN nanoparticle suspension includes the following steps: (1) Weigh 3.69 mg of Pr-2CN and dissolve it in 10 mL of tetrahydrofuran to obtain a concentration of 1×10⁻⁶. -3 A mol / L Pr-2CN organic phase solution.
[0035] (2) An appropriate amount of Pr-2CN organic phase solution was placed in the oil phase injection pump of the ultrasonic microreactor, and deionized water was placed in the aqueous phase injection pump. The volume ratio of the aqueous phase to the oil phase was set to 20:1, the total flow rate was set to 21 mL / min, and the ultrasonic power was set to 24%. Under the above conditions, the organic phase and the aqueous phase were rapidly mixed, and Pr-2CN was precipitated by antisolvent and formed into nanoparticles by ultrasonic-assisted self-assembly, yielding a concentration of 5×10⁻⁶. -5 The mol / L Pr-2CN nanoparticle suspension appears as a light green, clear solution.
[0036] Example 2 A method for preparing a Pr-2CN nanoparticle suspension includes the following steps: (1) Weigh 1 mg of Pr-2CN and dissolve it in 27 mL of tetrahydrofuran to obtain a concentration of 1×10⁻⁶. -4 A mol / L Pr-2CN organic phase solution.
[0037] (2) An appropriate amount of Pr-2CN organic phase solution was placed in the oil phase injection pump of the ultrasonic microreactor, and deionized water was placed in the aqueous phase injection pump. The volume ratio of the aqueous phase to the oil phase was set to 9:1, the total flow rate was set to 10 mL / min, and the ultrasonic power was set to 30%. Under the above conditions, the organic phase and the aqueous phase were rapidly mixed, and Pr-2CN was precipitated by antisolvent and formed into nanoparticles by ultrasonic-assisted self-assembly, yielding a concentration of 1×10⁻⁶. -5 The mol / L Pr-2CN nanoparticle suspension appears as a light green, clear solution.
[0038] Example 3 A method for preparing a Pr-2CN nanoparticle suspension includes the following steps: (1) Weigh 3.69 mg of Pr-2CN and dissolve it in 20 mL of tetrahydrofuran to obtain a concentration of 5 × 10⁻⁶ mg. -4 A mol / L Pr-2CN organic phase solution.
[0039] (2) An appropriate amount of Pr-2CN organic phase solution was placed in the oil phase injection pump of the ultrasonic microreactor, and deionized water was placed in the aqueous phase injection pump. The volume ratio of the aqueous phase to the oil phase was set to 15:1, the total flow rate was set to 16 mL / min, and the ultrasonic power was set to 28%. Under the above conditions, the organic phase and the aqueous phase were rapidly mixed, and Pr-2CN was precipitated by antisolvent and formed into nanoparticles by ultrasonic-assisted self-assembly, yielding a concentration of 3×10⁻⁶. -5 The mol / L Pr-2CN nanoparticle suspension appears as a light green, clear solution.
[0040] Example 4 A method for preparing a Pr-2CN nanoparticle suspension includes the following steps: (1) Weigh 3.69 mg of Pr-2CN and dissolve it in 10 mL of acetonitrile to obtain a concentration of 1×10⁻⁶. -3 A mol / L Pr-2CN organic phase solution.
[0041] (2) An appropriate amount of Pr-2CN organic phase solution was placed in the oil phase injection pump of the ultrasonic microreactor, and deionized water was placed in the aqueous phase injection pump. The volume ratio of the aqueous phase to the oil phase was set to 20:1, the total flow rate was set to 21 mL / min, and the ultrasonic power was set to 24%. Under the above conditions, the organic phase and the aqueous phase were rapidly mixed, and Pr-2CN was precipitated by antisolvent and formed into nanoparticles by ultrasonic-assisted self-assembly, yielding a concentration of 5×10⁻⁶. -5 The mol / L Pr-2CN nanoparticle suspension appears as a light green, clear solution.
[0042] Comparative Example 1 A method for preparing a suspension of tetrahydroxyphenylporphyrin (THPP) nanoparticles includes the following steps: (1) Weigh 6.78 mg of THPP and dissolve it in 10 mL of tetrahydrofuran to obtain a concentration of 1×10⁻⁶ mg. -3 mol / L THPP organic phase solution.
[0043] (2) An appropriate amount of THPP organic phase solution was placed in the oil phase injection pump of the ultrasonic microreactor, and deionized water was placed in the aqueous phase injection pump. The volume ratio of the aqueous phase to the oil phase was set to 20:1, the total flow rate was set to 21 mL / min, and the ultrasonic power was set to 24%. Under the above conditions, the organic phase and the aqueous phase were rapidly mixed, and Pr-2CN was precipitated by antisolvent and then self-assembled by ultrasound to form nanoparticles, yielding a concentration of 5×10⁻⁶. -5 The mol / L Pr-2CN nanoparticle suspension appears as a light green, clear solution.
[0044] Comparative Example 2 A method for preparing Pr-2CN nanoparticle suspension using a conventional antisolvent precipitation method includes the following steps: (1) Weigh 3.69 mg of Pr-2CN and dissolve it in 10 mL of tetrahydrofuran to obtain a concentration of 1×10⁻⁶. -3 A mol / L Pr-2CN organic phase solution.
[0045] (2) Pr-2CN organic phase solution was added dropwise to deionized water under magnetic stirring, wherein the volume ratio of water phase to organic phase was 20:1, and Pr-2CN nanoparticle suspension was obtained.
[0046] Performance characterization and testing 1. Photophysical properties, particle size and morphology characterization Figure 1 In the figures (a), (b), and (c), the UV-Vis absorption spectrum, dynamic light scattering spectrum, and photoluminescence spectrum of the Pr-2CN organic phase solution (Solution) and nanoparticle suspension (NPs) prepared in Example 1 are respectively. Figure 1In the figure, (d), (e), and (f) are the UV-Vis absorption spectrum, dynamic light scattering spectrum, and photoluminescence spectrum of the THPP organic phase solution and nanoparticle suspension prepared in Comparative Example 1, respectively; where: the horizontal axis Wavelength represents wavelength, Size represents particle size; the vertical axis Normalized Absorbance represents normalized absorbance, Number (Percent) represents percentage, and Intensity represents peak intensity.
[0047] Depend on Figure 1 It is known that in tetrahydrofuran solution, the Soret band of Pr-2CN is located at 409 nm, the full width at half maximum (FWHM) is 61 nm, and the Q bands are located at 551 nm and 596 nm. After being fabricated into nanoparticles, the Soret band of Pr-2CN red-shifts, the FWHM broadens to 73 nm, and the Q band also red-shifts, with the two bands approximately merging to form a broad absorption range of 250-700 nm. Figure 1 a). Dynamic light scattering results show that the peak particle size (Suspension Average) of Pr-2CN nanoparticles is 407 nm, and the PDI is 0.337 ( Figure 1 b). Under 420 nm UV light irradiation, Pr-2CN nanoparticles exhibited significant fluorescence quenching. Pr-2CN in tetrahydrofuran solution showed a strong emission peak at 610 nm and a shoulder peak at 663 nm; after nanoparticle formation, the fluorescence was significantly quenched, and the emission peak red-shifted to 722 nm. Figure 1 c). Similarly, in tetrahydrofuran solution, the Soret band of THPP is located at 423 nm, and it exhibits four well-separated Q band absorption peaks at 519, 557, 597, and 653 nm. After being fabricated into nanoparticles, the full width at half maximum (FWHM) of the Soret band of THPP broadened from 12 nm to 52 nm, and the Q band changed from four peaks to three and exhibited a red shift (c). Figure 1 d), with a particle size of 67 nm and a PDI of 0.208 ( Figure 1 e). THPP has two emission peaks in the solution phase. After being converted into NPs, the peak positions remain unchanged, only the emission intensity decreases. Figure 1 f).
[0048] Figure 2 Field emission scanning electron microscope (FESEM) images of Pr-2CN (a) and THPP (b) nanoparticles prepared in Example 1 and Comparative Example 1 show that the Pr-2CN nanoparticles have a rhomboid or near-rhomboid morphology, with relatively clear particle boundaries, and some particles exhibit a certain degree of fusion. Figure 2 a); THPP nanoparticles are spherical, exhibit significant aggregation, and have a smaller particle size ( Figure 2 (b) However, both still retain the characteristics of nano-aggregates.
[0049] The above results show that Pr-2CN can form a stable nanoscale suspension system after nanoscale self-assembly and significantly broaden its visible light absorption range.
[0050] Figure 3 The images shown are of the Pr-2CN nanoparticle suspensions prepared in Example 1 and Comparative Example 2. Figure 3 As can be seen, in Example 1, the organic phase and the aqueous phase come into rapid contact in a microchannel confinement environment and achieve efficient mixing under ultrasonic cavitation, enabling the system to form a relatively uniform supersaturated state in a short time, which is conducive to the simultaneous occurrence of nucleation and growth processes. The prepared Pr-2CN nanoparticle suspension is clear in appearance, with no visible particle precipitation. Figure 3 a). In contrast, Comparative Example 2 mainly relies on macroscopic stirring and molecular diffusion to complete mixing, resulting in a larger local concentration gradient. This makes it difficult to synchronize nucleation and growth processes, easily leading to secondary particle aggregation and a wider particle size distribution. Larger particles can be observed precipitating in the resulting suspension. Figure 3 (b) This result indicates that the ultrasonic microreactor preparation method differs from the traditional precipitation method. Instead, it utilizes the synergistic effect of fluid dynamics and ultrasonic cavitation to regulate the nucleation, growth, and aggregation processes of Pr-2CN, thereby improving the dispersibility and uniformity of the nanoparticle suspension.
[0051] 2. Photocatalytic degradation of crystal violet by Pr-2CN nanoparticles Crystal violet (CV) was used as a model pollutant, and its structural formula is as follows: Figure 4 (a) The photocatalytic degradation performance of the Pr-2CN and THPP nanoparticle suspensions prepared in Example 1 and Comparative Example 1 was evaluated. A schematic diagram of the degradation process is shown in Figure 1. Figure 4 As shown in b. During the degradation process, the Pr-2CN and THPP nanoparticle suspensions prepared in Example 1 and Comparative Example 1, respectively, were added to crystal violet to obtain the test solution (CV Solution), wherein the concentration of CV was 2.5 × 10⁻⁶. -5 The concentration of Pr-2CN / THPP NPs is 1×10 mol / L. -5 mol / L. 3.4 mL of the test solution was added to a 10 mm cuvette. Before the reaction, the cuvette was placed in the dark (Dark Adsorption) for 45 min to reach dark adsorption equilibrium. Then, it was irradiated with a 410 nm LED lamp (Irradiation) for 0-60 min to carry out the photocatalytic reaction. During the irradiation process, the UV-Vis absorption spectrum of the system was recorded. The degradation efficiency was calculated by the change in the intensity of the characteristic absorption peak of crystal violet at 582 nm. The results are as follows: Figure 5 As shown.
[0052] Depend on Figure 5 It can be seen that under 410 nm LED illumination, the characteristic absorption peak of crystal violet at 582 nm gradually decreases with increasing illumination time; after 1 hour of illumination, the degradation rate of crystal violet by Pr-2CN nanoparticles reaches 54.6%. Figure 5 c). During the degradation process, isoabsorption points appear in the absorption spectrum ( Figure 5 a) This indicates that crystal violet molecules undergo structural transformation and degradation under photocatalysis.
[0053] To eliminate the influence of photolysis and dark adsorption of crystal violet on the results, a blank control experiment without Pr-2CN nanoparticles was set up, and the results are as follows. Figure 6 As shown. By Figure 6 It can be seen that in the absence of Pr-2CN nanoparticles, the self-photolysis of crystal violet under the same illumination conditions is not significant. Figure 6 a); Under dark conditions, the adsorption contribution of Pr-2CN nanoparticles to crystal violet is limited ( Figure 6 b). This indicates that the decrease in crystal violet concentration mainly originates from the photocatalytic degradation process initiated by Pr-2CN nanoparticles under light irradiation.
[0054] The photocatalytic degradation performance of THPP nanoparticles prepared using Comparative Example 1 was tested under the same conditions. The results showed that the degradation rate of crystal violet by THPP nanoparticles was slower, while the degradation efficiency of Pr-2CN nanoparticles was more than twice that of THPP nanoparticles. Figure 5 (b) This result indicates that, compared with THPP nanoparticles, Pr-2CN nanoparticles exhibit higher catalytic activity in visible light-driven degradation of organic pollutants.
[0055] 3. Photocatalytic degradation of crystal violet by Pr-2CN nanoparticles under different atmospheres This test was conducted to illustrate the effect of oxygen on the photocatalytic degradation of crystal violet by Pr-2CN nanoparticles. A mixture of Pr-2CN nanoparticles and crystal violet was prepared according to the method described above, achieving a crystal violet concentration of 2.5 × 10⁻⁶. - 5 The concentration of Pr-2CN nanoparticles was 1×10 mol / L. -5 mol / L. Three sets of experiments were set up under nitrogen atmosphere, oxygen-enriched atmosphere, and air atmosphere, respectively. The results are as follows: Figure 7 As shown in (a), (b) and (c) in the figure.
[0056] During illumination, the absorption peak change of crystal violet at 582 nm was recorded, and the degradation efficiency under different atmospheres was calculated. The results showed that after 1 hour of illumination, the degradation efficiency of Pr-2CN nanoparticles for crystal violet significantly decreased under a nitrogen atmosphere, with a degradation rate of approximately 10%; under an air atmosphere, crystal violet could be effectively degraded; and under an oxygen-rich atmosphere, the degradation efficiency further improved, reaching 84%. Figure 7 c).
[0057] The above results indicate that oxygen participates in the photocatalytic degradation of crystal violet by Pr-2CN nanoparticles. Compared with a nitrogen atmosphere, both air and oxygen-enriched atmospheres are beneficial to improving the photocatalytic degradation efficiency, suggesting that the photocatalytic reaction in this system is closely related to the participation of oxygen in the generation of reactive oxygen species.
[0058] 4. Comparative examples and photostability tests of homogeneous systems This test was conducted to demonstrate that the stability of Pr-2CN under illumination is improved after nano-assembly. A Pr-2CN nanoparticle suspension was prepared according to the method in Example 1, with a Pr-2CN tetrahydrofuran solution used as a homogeneous control. Both the Pr-2CN nanoparticle suspension and the Pr-2CN tetrahydrofuran solution were irradiated under the same illumination conditions, and the changes in their UV-Vis absorption spectra were recorded at different illumination times.
[0059] For the Pr-2CN tetrahydrofuran solution, the Soret absorption peak decreased significantly with increasing illumination time during the illumination process, indicating that Pr-2CN molecules are prone to self-photolysis or photodegradation in homogeneous solutions. Figure 8 a). Meanwhile, this homogeneous system did not exhibit significant photocatalytic degradation activity for crystal violet ( Figure 8 b).
[0060] In contrast, the main absorption peak of the Pr-2CN nanoparticle suspension did not show significant attenuation under the same illumination time, indicating that Pr-2CN in the nanoparticle state has better photostability. Figure 5 a) Based on the photocatalytic degradation results, it can be seen that after Pr-2CN is prepared into nanoparticles, it can not only maintain high photostability, but also effectively degrade crystal violet under visible light irradiation.
[0061] 5. Detection and quenching experiments of reactive oxygen species generated by Pr-2CN nanoparticles This test was conducted to demonstrate that Pr-2CN nanoparticles can generate reactive oxygen species under illumination, and to further clarify the main types of reactive species. The ability of Pr-2CN nanoparticles to generate reactive oxygen species under illumination was detected using a fluorescent probe method. Singlet Oxygen Sensor Green (SOSG) was selected as the singlet oxygen probe, Hydroxyphenyl Fluorescein (HPF) as the hydroxyl radical probe, and Dihydrorhodamine 123 (DHR123) as the superoxide anion radical probe.
[0062] The Pr-2CN nanoparticle suspension was mixed with the above-mentioned fluorescent probes, and the tests were performed under 410 nm LED illumination. The results are as follows: Figure 9 As shown in (a), (b), and (c) of the figure, the fluorescence intensity of all three probe systems containing Pr-2CN nanoparticles increased with increasing illumination time under 410 nm illumination. This indicates that Pr-2CN nanoparticles can generate reactive oxygen species such as singlet oxygen, hydroxyl radicals, and superoxide anion radicals under illumination. The blank control experiment showed that the fluorescence enhancement caused by the probe's self-oxidation was weak in the absence of Pr-2CN nanoparticles, thus eliminating the main influence of probe self-oxidation on the results.
[0063] Further detection of reactive oxygen species using electron paramagnetic resonance (ENR) technology yielded the following results: Figure 10 As shown in (a), (b), and (c), where the horizontal axis represents the magnetic field. Using TEMP as a singlet oxygen scavenger and DMPO as a free radical scavenger, the electron paramagnetic resonance signal of the Pr-2CN nanoparticle system was tested under 410 nm illumination (Light). The results show that characteristic signals of singlet oxygen, superoxide anion radicals, and hydroxyl radicals can be observed after illumination, and the signal intensity is significantly higher than under dark conditions.
[0064] To determine the contribution of different reactive oxygen species in the degradation of crystal violet, quenching experiments were further conducted. Isopropanol, p-benzoquinone, and triphenylamine were added as quenchers for hydroxyl radicals, superoxide anion radicals, and singlet oxygen, respectively. The results showed that the degradation efficiency of crystal violet was significantly inhibited after the addition of p-benzoquinone and triphenylamine, indicating that superoxide anion radicals and singlet oxygen play a major role in the degradation of crystal violet; their contribution order was: singlet oxygen > superoxide anion radical > hydroxyl radical. Figure 10 d).
[0065] Figure 11The figure shows the frontier molecular orbital calculation results for the Pr-2CN nanoparticle suspension prepared in Example 1. Density functional theory calculations show that the HOMO of Pr-2CN is mainly delocalized throughout the molecular framework, while the LUMO is mainly distributed in the bottom conjugated aromatic fused ring region. This frontier orbital distribution is conducive to intramolecular charge transfer and charge separation under photoexcitation, thus providing a basis for electron transfer to oxygen and the generation of superoxide anion radicals.
[0066] 6. Excited-state kinetics of Pr-2CN nanoparticles Figure 12 The femtosecond transient absorption spectra of the Pr-2CN organic phase solution and nanoparticle suspension prepared in Example 1 are shown.
[0067] This test was used to illustrate the excited-state dynamics basis of the improved photostability and reactive oxygen species generation capacity of Pr-2CN nanoparticles. Femtosecond transient absorption spectroscopy was used to test the excited-state evolution of Pr-2CN in both the tetrahydrofuran solution phase and the nanoparticle state. During the test, the excitation wavelength was set to 420 nm, the excitation power was 0.3 mW, and the detection range covered 320-780 nm. A Pr-2CN tetrahydrofuran solution was used as a solution control, and the Pr-2CN nanoparticle suspension obtained in Example 1 was used as the nano-aggregate sample. The results are as follows: Figure 12 As shown.
[0068] like Figure 12 As shown in (a)-(c), the transient absorption spectra of the solution-phase Pr-2CN show that transient absorption peaks appear at 330 nm and 518 nm at 539 fs, attributed to excited singlet state absorption; within 253 ps, the signal at 330 nm decays while the signal at 518 nm remains essentially unchanged; after 253 ps, both peaks decay, but neither fully returns to the baseline, indicating the presence of long-lived triplet species. The negative absorption near 420 nm originates from excitation light scattering, while the negative absorptions near 420 nm and 600 nm are attributed to ground-state bleaching. The transient absorption signals of Pr-2CN nanoparticles are relatively weak, such as... Figure 12 The values (d) and (e) in the figure may be related to their low molar extinction coefficients. Excited singlet absorption peaks (345 nm, 536 nm, 584 nm) were observed at 476 fs, followed by a decay process. The excited-state evolution behavior of nanoparticles is simpler than that in the solution phase. A tri-exponential fit was then performed on the main absorption peaks, yielding the data in Table 1.
[0069] Table 1:
[0070] Table 1 shows that for the Pr-2CN tetrahydrofuran solution, multi-exponential fitting of the kinetics at 518 nm yielded three main lifetime components. τ1 (0.13 ps) corresponds to the excited state formation process; τ2 (144 ps) corresponds to the vibrational relaxation and solvation rearrangement process of the singlet excited state; and τ3 (2610 ps) corresponds to the intersystem crossing process from S1 to T1. Furthermore, the fitting also revealed a long-lived component, indicating the presence of certain long-lived excited-state species in the solution phase.
[0071] For the Pr-2CN nanoparticle suspension, excited-state absorption signals were also observed in the femtosecond transient absorption spectrum. Multi-exponential fitting of the kinetics at 535 nm yielded τ1 of 0.16 ps, τ2 of 23.6 ps, and τ3 of 371 ps. Here, τ2 corresponds to the vibrational relaxation process, and τ3 corresponds to the intersystem crossing process. Compared to the solution phase, the vibrational relaxation time in the Pr-2CN nanoparticles decreased from 144 ps to 23.6 ps, and the intersystem crossing time decreased from 2610 ps to 371 ps.
[0072] The results show that the excited-state decay process of Pr-2CN is significantly accelerated after it forms nanoparticles. In the nano-aggregate state, the intermolecular distance is shortened and the intermolecular interactions are enhanced, which facilitates energy or charge transfer between excitons between adjacent molecules, thereby promoting rapid excited-state decay. This process can reduce the accumulation of long-lived excited-state species and help improve the photostability of Pr-2CN nanoparticles.
[0073] Meanwhile, Pr-2CN nanoparticles can still generate some triplet excited states through intersystem crossing. These triplet excited states can further undergo energy transfer or electron transfer with oxygen to generate reactive oxygen species such as singlet oxygen, superoxide anion radicals, and hydroxyl radicals. This result is consistent with the reactive oxygen species detection results, indicating that Pr-2CN nanoparticles possess both good photostability and reactive oxygen species generation capacity, and their photocatalytic degradation performance of organic pollutants has a clear excited-state kinetic basis.
[0074] 7. Photocatalytic degradation of different organic pollutants by Pr-2CN nanoparticles This test was conducted to demonstrate the photocatalytic degradation ability of Pr-2CN nanoparticles for different types of organic pollutants. Except for replacing crystal violet with rhodamine B (RhB) or tetracycline (TC), the remaining experimental procedures were the same as those for the crystal violet photocatalytic degradation test. The results are as follows: Figure 10 As shown in (e) and (f) in the figure. The results show that Pr-2CN nanoparticles also exhibit degradation effects on rhodamine B and tetracycline, indicating that this phthalocyanine-based nanoaggregate material has a certain applicability for the removal of organic pollutants.
[0075] For those skilled in the art, several simple deductions or substitutions can be made without departing from the inventive concept, without requiring creative effort. Therefore, any simple improvements made to this invention by those skilled in the art based on the disclosure of this invention should be within the scope of protection of this invention. The above embodiments are preferred embodiments of this invention, and all processes similar to this invention and equivalent changes should fall within the scope of protection of this invention.
Claims
1. A method for preparing a photocatalyst, characterized in that, Includes the following steps: (1) Dissolve phthaloyl compounds in an organic solvent to obtain an organic phase solution of phthaloyl; (2) The phthalocyanine organic phase solution and the aqueous phase are respectively fed into the ultrasonic microreactor, so that the phthalocyanine compounds are precipitated in the aqueous phase by continuous flow antisolvent under ultrasonic assistance, and self-assembled to form a nanoparticle suspension, thus obtaining the photocatalyst.
2. The method for preparing the photocatalyst according to claim 1, characterized in that, The phthaloyl compounds include dicyano-substituted phthaloyl Pr-2CN.
3. The method for preparing the photocatalyst according to claim 1 or 2, characterized in that, The organic solvent is selected from at least one of tetrahydrofuran, acetonitrile, and N,N-dimethylformamide; and / or the aqueous phase is selected from deionized water or an aqueous solution containing a surfactant.
4. The method for preparing the photocatalyst according to claim 3, characterized in that, The concentration of the phthalocyanine organic phase solution is 1×10⁻⁶. -4 -1×10 -3 mol / L.
5. The method for preparing the photocatalyst according to claim 1, characterized in that, The volume ratio of the phthalocyanine organic phase solution to the aqueous phase is 1:(9-20), and the total flow rate of the phthalocyanine organic phase solution and the aqueous phase is 10-21 mL / min.
6. A photocatalyst, characterized in that, The photocatalyst is prepared by the preparation method according to any one of claims 1-5, wherein the photocatalyst is a nanoparticle suspension of phthalocyanine compounds in an aqueous phase.
7. The photocatalyst according to claim 6, characterized in that, The average particle size of the nanoparticles in the nanoparticle suspension is 300-500 nm.
8. The photocatalyst according to claim 7, characterized in that, The nanoparticles have a rhomboid or rhomboid shape.
9. The application of the photocatalyst according to any one of claims 6-8 in the photocatalytic degradation of organic pollutants.
10. The application according to claim 9, characterized in that, The organic pollutant is selected from one of crystal violet, rhodamine B, and tetracycline; and / or the photocatalytic degradation is carried out in an air atmosphere or an oxygen-enriched atmosphere.